DETEKSI GEN TEM DAN GEN SHV PADA Klebsiella pneumoniae PADA SAMPEL URIN PASIEN RAWAT INAP - Ade Irma; Nurul Fathoana; Ka’bah Ka’bah (Klinikal Sains : Jurnal Analis Kesehatan, 2024)
One of the main causes of healthcare-related infections is the incidence of infections due to Klebsiella pneumonia which commonly causes pneumonia, bacteremia, and urinary tract infections (UTIs). An increased risk of infection with Klebsiella pneumonia bacteria is associated with the emergence of antibiotic resistance genes. The emergence and spread of antibiotic-resistant genes, reduces the chances of treatment and increases mortality and morbidity. This study aimed to detect the TEM gene and SHV gene in Klebsiella pneumonia in the urine of hospitalized patients. The type of research used was laboratory observation with a cross sectional study approach using the Polymerase Chain Reaction method with 15 urine samples of hospitalized patients. The results of this study found 6 positive samples (40%) of Klebsiella pneumonia in the urine of hospitalized patients with a target size of 260bp. Then proceed with the detection of the TEM gene and SHV gene. Found 1 positive sample of TEM gene (16.6%) with a target size of 445bp and 4 positive samples of SHV gene (66.6%) with a target size of 747bp. The conclusion of this study was found TEM and SHV genes in Klebsiella pneumonia that were resistant to sepalosphorin antibiotics in hospitalized patients.